Smart fertilizers: what should we mean and where should we go? - Giorgia Raimondi; Carmelo Maucieri; Arianna Toffanin; Giancarlo Renella; Maurizio Borin (Italian Journal of Agronomy, 2021)
Highlights - A smart fertilizer allows to control the rate, timing and duration of nutrients release. - Nanofertilizers are powder or liquid formulations which involve the synthesis, design and use of materials at the nanoscale level. - Composite fertilizers are formulations containing nutrients mixed or coated with one or more materials that exploit synergy among materials. - Bioformulations are fertilizers containing active or dormant microorganisms capable to trigger physiological growth responses in plants. - Limited information is available for smart fertilizers on herbaceous crops in open field conditions.